Composing A Care of the Self - Carlson, David Lee. author. aut Link
XXXII, 228 p.
Keywords: What do Germ Theory, self-psychology, the entrepreneur and the Bertillion Card have in common? They comprise a part of the historical dispositif for the emergence of the writing portfolio. This riveting Foucaultian-inspired genealogy travels through the history of medicine, criminality, psychology, political economics to reveal the epistemologies and practices of power/knowledge of the contemporary portfolio. In so doing, it challenges previous held beliefs about the germination of the secondary school, prevailing views of the dawning of secondary English as a discipline, and most important, the costs and effects of progressivist’s writing pedagogies and assessment instruments. Carlson & Albright offer fresh and far-ranging examinations of the rise and development of composition studies and assessment practices in U.S. secondary schools, thereby challenging major English education scholars’ long-held interpretations of such. Composing a Care of the Self: A Critical History of Writing Assessment in Secondary English Education posits, for example, an elucidation of the history of writing assessment that I believe is most compelling and original, particularly in its analysis of historically dominant medical discourses and metaphors of the late 19th century and their influences on secondary English educators. Further, the authors, inspired by Foucault’s uses of genealogy as means to expose practices and rationalities of power/knowledge dynamics and their relations to matters of governance, dramatically advance theoretical orientations within the field of English Education. They do so through their intricate weaving of Foucauldian theoretical perspectives into analyses of crucial and yet often taken-for granted forms and functions of composition studies and writing assessments in the secondary English classroom. As such, this book is a remarkable achievement. - Janet L. Miller, Ph.D. Professor, Programs in English & Education Teachers College, ColumbiaUniversity In COMPOSING A CARE OF THE SELF: A CRITICAL HISTORY OF WRITING ASSESSMENT IN SECONDARY ENGLISH EDUCATION David Carlson and James Albright problematized secondary school assessment practices in the late nineteenth century and provide a fascinating genealogical study of English education. Together and under the mantle of Foucaultian genealogy they explore the relationships among the body, health, and secondary education exploring how epistemology in medicine spread to educational discourse. This is a highly readable account and one that disturbs the standard histories. It is a highly recommended text for all those interested in the history of English studies and writing assessment. - Michael A. Peters, Professor Emeritus, University of Illinois, Professor, Policy, Cultural & Social Studies in Education, University of Waikato.